Pneumotonometer Accuracy Using Manometric Measurements after Radial Keratotomy, Clear Corneal Incisions and Lamellar Dissection in Porcine Eyes. (2nd January 2020) - Maloley, Lauren A.; Razeghinejad, M. Reza; Havens, Shane J.; Gulati, Vikas; Fan, Shan; High, Robin; Ghate, Deepta A.
ABSTRACT: Purpose/Aim of the study: Measured intraocular pressure (IOP) after corneal incisions may not be reflective of the true IOP because of changes in corneal biomechanical properties. The purpose of this study is to investigate the effect of various corneal incisions on pneumotonometer accuracy in enucleated porcine eyes. Materials and Methods: A pneumotonometer was used to measure IOP (IOPp) at manometrically controlled pressure levels of 10, 20, 30 and 40 mmHg in enucleated porcine eyes. IOP measurements at each level were repeated after one of the following corneal incisions: radial keratotomy (8 eyes), lamellar dissection (10 eyes), clear cornea standard phacoemulsification incisions (10 eyes). The pneumotonometer error, defined as the difference between IOPp and manometric pressure (IOPm), was calculated for each pressure level. The error before the corneal incisions was compared to the error after the corneal incisions to assess the accuracy of the pneumotonometer. Results: The pneumotonometer underestimates true IOP at all pressure levels, both before and after the corneal procedures. There was a statistically significant greater underestimation of IOP after radial keratotomy incisions at pressure levels of 20, 30 and 40 mmHg ( p = .013, 0.004, and 0.002, respectively). There was no statistically significant difference in the amount of pneumotonometer underestimation error after lamellar dissection or standard cataract incisions. Conclusion: The pneumotonometer underestimates true IOP in enucleated porcine eyes at all pressure levels between 10–40 mmHg. Radial keratotomy incisions caused a statistically significant greater underestimation error in pneumotonometry measurements at pressures of 20–40 mmHg. Lamellar dissection and clear corneal cataract incisions did not cause an additional error in pneumotonometry measurements in enucleated porcine eyes.